Determination of yarn length in a loop based on the technological parameters of the machine - Đorđević Miodrag; Stanković Viktorija; Ilić Ana (Tekstilna industrija, 2020)
Yarn length in a loop is one of the most important technological parameters in knitwear structure analysis. Therefore, determination of the accurate values of yarn length in a loop is of great importance in knitwear structure parameters projection. This paper presents comparative results of the determination of yarn length in a loop based on the loop row height, loop row width and calculated yarn diameter, as well as determination of loop length based on machine technological parameters taking into account needle pace, platinum and needle diameter, platinum and needle curved radius, span angle of yarn with needle and platinum and projected cooling depths. The results obtained show various values of yarn length in a loop.